-7x+6+5x=-3x+11

Simple and best practice solution for -7x+6+5x=-3x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+6+5x=-3x+11 equation:


Simplifying
-7x + 6 + 5x = -3x + 11

Reorder the terms:
6 + -7x + 5x = -3x + 11

Combine like terms: -7x + 5x = -2x
6 + -2x = -3x + 11

Reorder the terms:
6 + -2x = 11 + -3x

Solving
6 + -2x = 11 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
6 + -2x + 3x = 11 + -3x + 3x

Combine like terms: -2x + 3x = 1x
6 + 1x = 11 + -3x + 3x

Combine like terms: -3x + 3x = 0
6 + 1x = 11 + 0
6 + 1x = 11

Add '-6' to each side of the equation.
6 + -6 + 1x = 11 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 11 + -6
1x = 11 + -6

Combine like terms: 11 + -6 = 5
1x = 5

Divide each side by '1'.
x = 5

Simplifying
x = 5

See similar equations:

| 6x^2+15x+27=0 | | 3x-6+6(x+1)=7x+2 | | 10x^2+16x+24=0 | | x+12=2x+5 | | -3x^3-6x=0 | | 2-7(y+2)=9-3y | | -7[5+3(6+9)]= | | (6y^3-y^2+4)(4y^2+y+1)= | | -7x+7+5x=-3x+12 | | 8.5p=7.5p | | -7x+4+5x=-3x+9 | | 0.2(x+1)=0.3(x+11) | | -6(x+1)+2(7x+9)= | | 2x+149=9x-5 | | 9-4(y+7)=7+3y | | x^4+9x^2+400=0 | | 3b-2=19 | | 2x-3+5x=4+4x+1 | | 2x+y-2z=2 | | s^2+9s+81=0 | | 7*6= | | 89-7x=29x+21 | | X^3=81x | | x-4y+2z=-11 | | 26=7x+x+2 | | 30-5a=10 | | -.5(y+5)=-1 | | c/8+10=15 | | 3x+2y-4z=3 | | c/8=15 | | 12x^2+12x-24=0 | | 12-10x=62-24x |

Equations solver categories